1997
DOI: 10.1007/s002709900147
|View full text |Cite
|
Sign up to set email alerts
|

Injection-associated pain in femoral arteriography: A European multicenter study comparing safety, tolerability, and efficacy of iodixanol and iopromide

Abstract: Iodixanol 270 mg I/ml causes significantly less injection-associated pain during femoral arteriography and is as safe and efficacious as iopromide 300 mg I/ml.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
19
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 15 publications
9
19
0
1
Order By: Relevance
“…Several studies compared image enhancement of iodixanol with the higher-iodine-concentration agent [4][5][6][7][8]. They reported that iodixanol showed similar enhancement in the aorta and peripheral vessels.…”
mentioning
confidence: 99%
“…Several studies compared image enhancement of iodixanol with the higher-iodine-concentration agent [4][5][6][7][8]. They reported that iodixanol showed similar enhancement in the aorta and peripheral vessels.…”
mentioning
confidence: 99%
“…Finally, osmolarity of intra-arterial contrast media has been shown to affect patient comfort during extremity angiography. 7 For this reason, iso-osmolar contrast is frequently used for upper-and lower-extremity runoff studies.…”
Section: Intravascular Contrast Administrationmentioning
confidence: 99%
“…23,24 Several studies that have compared the tolerability of the iso-osmolar contrast medium iodixanol with that of lowosmolar contrast medium report that iso-osmolar contrast medium is associated with a decrease in the intensity of discomfort (heat sensations) and pain. [24][25][26][27][28][29][30] Overall, the key issue that becomes important to define for each specialty is the degree of risk that makes the effort needed to screen patients, identify those at risk, and then implement prevention strategies, a requirement despite any impracticality.…”
Section: The Need For Specialty-specific Guidelinesmentioning
confidence: 99%